2018
DOI: 10.3389/fimmu.2018.01836
|View full text |Cite
|
Sign up to set email alerts
|

Human CARD9: A Critical Molecule of Fungal Immune Surveillance

Abstract: CARD9 is a signaling adaptor protein that is involved in the transduction of signals from a variety of innate pattern recognition receptors, including the C-type lectin receptors and intracellular NOD receptors and nucleic acid sensors. As a result, CARD9 has been shown in animal models to be an important regulator of immunity to bacteria, fungi, and viruses. Studies in humans with autosomal recessive CARD9 deficiency have indicated a highly specific role for this molecule in the activation of antifungal immun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
104
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 118 publications
(105 citation statements)
references
References 57 publications
1
104
0
Order By: Relevance
“…21 Dectin-1 is a pattern recognition receptor that recognizes the components of the fungal cell wall. 45 CARD9 signaling occurs in response to the recognition of fungal ligands by Dectin-1. Alterations in Dectin-1 have been associated with medically refractory ulcerative colitis (UC).…”
Section: The Microbiome and Inflammatory Bowel Diseasementioning
confidence: 99%
See 1 more Smart Citation
“…21 Dectin-1 is a pattern recognition receptor that recognizes the components of the fungal cell wall. 45 CARD9 signaling occurs in response to the recognition of fungal ligands by Dectin-1. Alterations in Dectin-1 have been associated with medically refractory ulcerative colitis (UC).…”
Section: The Microbiome and Inflammatory Bowel Diseasementioning
confidence: 99%
“…46 CARD9 is also required for inflammatory cytokine production in response to specific bacterial stimuli and viral infection. 45 IL-6, TNF-a, and IL-1b are cytokines that are dependent on CARD9 function and are protective against fungal infection. 45 CARD9 knockout mice are susceptible to Candida albicans, Aspergillus fumigatus, and Cryptococcus neoformans among other fungi.…”
Section: The Microbiome and Inflammatory Bowel Diseasementioning
confidence: 99%
“…Caspase recruitment domain-containing protein 9 (CARD9) is mainly expressed in myeloid cells [58,59] and is an important adaptor protein in innate immunity, as it regulates innate immunity and affects adaptive immune responses [60,61]. Qu et al demonstrated the role of CARD9 in the development of LC for the first time.…”
Section: Caspase Recruitment Domain-containing Proteinmentioning
confidence: 99%
“…Caspase recruitment domain-containing protein 9 (CARD9) is a signalling adaptor protein involved in integrating signals from a range of innate receptors, including REVIEW SERIES: TRANSLATING IMMUNOMETABOLISM C-type lectin and nucleotide-binding oligomerization domain-like (NOD) receptors, and is thus involved in bacterial, viral and fungal immune responses [106]. CARD9 deficiency was found to affect gut microbial composition and had a resultant effect on tryptophan metabolism [107].…”
Section: Metabolic Interplay Between Host Microbiota and Pathogensmentioning
confidence: 99%